MENINGKATKAN KEMAMPUAN MEMBACA DAN MEMAHAMI KANDUNGAN AL-QUR’AN SURAT AL HUJURAT AYAT 13 DALAM MEMBINA UKHUWAH ISLAMIYAH MELALUI MODEL PEMBELAJARAN KOOPERATIF TEKNIK PENUGASAN - M Thoha (LPPM UNISDA, 2018)
This study aims to determine whether the cooperative learning model of assignment technique can improve the ability to read and understand the content of Surat Al-Hujurat Verse 13 in establishing Islamic Religion Islamic Religion subject for grade 6 students of SD Negeri Kembangbahu I, Kembangbahu Subdistrict, Lamongan Regency. The subjects of this study are all the fourth grade of SD Negeri Kembangbahu I, with the number of students 10 students. This study belongs to a classroom action research consisting of several cycles with each cycle consisting of planning, action, observation, and reflection. Instruments used in the form of observation sheets, questionnaires, and test sheets. The results showed an increase in student learning outcomes. In cycle I the average value of 54% and increased in cycle II to 69% and finally in cycle III to 86%. So there is an increase in the average value of 32%. It can be concluded that there is influence of the use of cooperative learning model of assignment technique to increase student's learning motivation and learning result so that indirectly the learning quality of Islamic Religious Education can increase.